2021
DOI: 10.1017/s0022215121002085
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction at six months after coronavirus disease 2019 infection

Abstract: Objective This study aimed to assess olfactory dysfunction in patients at six months after confirmed coronavirus disease 2019 infection. Methods Coronavirus disease 2019 positive patients were assessed six months following diagnosis. Patient data were recoded as part of the adapted International Severe Acute Respiratory and Emerging Infection Consortium Protocol. Olfactory dysfunction was assessed using the University of Pennsylvania Smell Identification Test. Results F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
(53 reference statements)
1
7
1
Order By: Relevance
“…Eight months later around 25% still reported chemosensory impairments. This magnitude is in line with the reports on persisting subjective chemosensory disorders months after COVID-19 [ 8 12 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Eight months later around 25% still reported chemosensory impairments. This magnitude is in line with the reports on persisting subjective chemosensory disorders months after COVID-19 [ 8 12 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Until now, still there are only few publications in which valid and reliable olfactory psychophysical tests have been used to assess smell in the long-term after COVID-19, and this is even less so for gustatory function [ 12 , 14 , 17 ]. In the present study, we assessed olfactory and gustatory function eight months after acute COVID-19 both through self-report and psychophysical tests, in order to quantify the prevalence of hyposmia and hypogeusia in post-COVID-19 condition.…”
Section: Introductionmentioning
confidence: 99%
“…Leedman et al. [ 66 ] reported that in a consecutive series of 56 patients with proven COVID-19, 64% were normosmic, 4% were anosmic, and 32% were hyposmic at 6 months, based on evaluation with UPSIT tests. In a case–control study of 100 patients with a median follow-up of 401 days after infection, olfactory dysfunction was found in 46% of affected and 10% of control subjects [ 67 ].…”
Section: Recovery Of Olfactory Loss After Covid-19mentioning
confidence: 99%
“… 1 , 15 The latter study retested 86 of the patients and found that the prevalence rate decreased to 39% 6 to 8 weeks after symptom onset, a value somewhat lower than the 3-month prevalence rate of the present study. González et al 16 noted a 73% prevalence rate for 100 COVID-19 Chilean patients tested with the UPSIT ® during the acute phase of the disorder which decreased to 41% for those tested a month later, the latter being similar to the 6 to 8 weeks prevalence observed by Moein et al 1 In a study of 56 Australian COVID-19 patients 6 months after their diagnosis, Leedman et al 17 found 35.6% exhibited some degree of smell loss. Boscolo-Rizzo et al 18 noted, using a modified version of the UPSIT ® , that 60% of 87 Italian patients tested 6 months after the COVID-19 diagnosis still had some degree of smell dysfunction.…”
Section: Discussionmentioning
confidence: 72%